Influence of thermomechanical processing on the cold deformability of low-carbon steel - Baručija, Besim (Materiali in tehnologije, 2013)
The group of steels intended for the production of bolts and nuts from the production programme of the Zenica Steel Plant, Zenica, nowadays called Arcelor Mittal Zenica, includes, among others, the steel C8C according to EN 10263-2. In this paper, the results of testing the above-mentioned steel, with the nitrogen content of more than 0.007 %, manufactured within a specifically defined technological programme, are presented. The testing of the rolled bars with a diameter of 12 mm is focused, among the mechanical and metallographic tests, especially on the technological compression test in the cold state that is normally performed as an additional control test in the production. The cold compression of the test samples has been performed in four degrees of deformation and at two different speeds of compressing tools. We determined the dependence of the resistance to deformation of the material on the degree and speed of deformation. The surface inspection of the tested samples was performed with visual control with the aim to determine deformability of the bars produced in this way.
Keywords: maloogljično jeklo; deformacija; stiskanje; karakterizacija materialov